(untitled) (Journal of Asian Development Studies, 2026)
This paper aims to examine the importance of informal sector as the last resort for employment during an economic crisis with Indonesia as the case study. Since its independence in 1945, Indonesia had experienced two big economic crises, namely the 1997/98 Asian financial crisis and the 2008/09 global economic crisis. The paper is based on secondary data analysis and a review of key literature on the crises. During those two crises periods, total employment in the country was generally expected to decline or open unemployment to increase significantly. But, surprisingly, total employment increased, and open unemployment increased only slightly in 1998 and dropped during the 2008-2009 period. One reason was that many laid off workers from crises-affected companies ended in informal economic activites that led to the increase of informal employment.